Peut-on faire croire autrement les élèves ? Enjeux épistémologiques d'une modestie sur ce que croire veut dire - Sébastien Charbonnier (Nantes Université, 2018)
The tradition of liberation through knowledge, from Plato to the Encyclopedia (learning rationally makes us free and allows better action in the world), is the very political project of public education. In this context, the scientific disciplines make sense in the pupils' curriculum. However, it is interesting to think these emancipatory possibilities of knowledge without abounding in a somewhat exclusionary (and contemptuous) sharing between "believers" and "knowers" as the imaginary of "barbarism" can produce it (there are them "to enlighten" and us "the enlightened"). In this sense, this paper attempts to present the epistemological foundations of a philosophy of belief that allows us to analyze the determinations that lead us to believe this or that thing, and allows us to characterize the proper scientific way of producing justified beliefs. Thus, it is the aims of scientific learning that will be less confusing, we hope, with regard to our aspirations to live in a democracy.